Penerapan QR Code dalam Aplikasi Monitoring Peralatan Kerja Berbasis Web Pada PT. Perusahaan Listrik Negara Gardu Induk Tanjung Uban - Dwi Nurul Huda; Muhammad Syafi’i (Prosiding, 2022)
Monitoring is an important thing in a company to ensure that the activities being carried out can be monitored continuously so that the information can be reported to the leadership. The State Electricity Company (PLN) Tanjung Uban Substation is one of the sub-branches in the Riau Archipelago, especially Bintan. In monitoring activities for borrowing and returning equipment that is currently happening, it is not well organized because it is still done Microsoft excel. In the activities of borrowing and returning equipment, recording is only carried out in the loan data processing process, while returns are often not recorded. This creates ambiguity in the data because sometimes duplicate data occurs due to miscalculation of the existing equipment inventory due to the process of returning equipment that is not recorded. The impact is that during the process of calculating the equipment, there is a difference in calculations from the previous month and when reporting to the leadership, a re-sweeping of the borrowing and returning processes that occurred previously has to be carried out. Therefore, we need a work equipment monitoring application that can monitor the borrowing and return of equipment, so that management reporting can be done in real-time. Every piece of equipment owned by the Company will be affixed with a QR Code as an item code. This application was developed using MySQL database and PHP programming. The system development method used is the waterfall model. Application of the QR Code on the web-based Maintenance Work Equipment Monitoring Application at PT. PLN (Persero) Substation Tanjung Uban can assist the process of monitoring equipment and produce information regarding the status of borrowing and returning equipment relevantly.